Bromoacetic acid causes oxidative stress and uric acid metabolism dysfunction via disturbing mitochondrial function and Nrf2 pathway in chicken kidney. Issue 12 (26th August 2022) - Wu, Yuting; Liu, Jiwen; Liu, Shuhui; Fan, Wentao; Ding, Chenchen; Gao, Zhangshan; Tang, Zhihui; Luo, Yan; Shi, Xizhi; Tan, Lei; Song, Suquan
Abstract: Since the outbreak of COVID‐19, widespread utilization of disinfectants has led to a tremendous increase in the generation of disinfection byproducts worldwide. Bromoacetic acid (BAA), one of the common disinfection byproducts in the environment, has triggered public concern because of its adverse effects on urinary system in mammals. Nevertheless, the BAA‐induced nephrotoxicity and potential mechanism in birds still remains obscure. According to the detected content in the Taihu Lake Basin, the model of BAA exposure in chicken was established at doses of 0, 3, 300, 3000 μg/L for 4 weeks. Our results indicated that BAA exposure caused kidney swelling and structural disarrangement. BAA led to disorder in renal function (CRE, BUN, UA) and increased apoptosis (Bax, Bcl‐2, caspase3). BAA suppressed the expression of mitochondrial biogenesis genes (PGC‐1α, Nrf1, TFAM) and OXPHOS complex I genes (ND1, ND2, ND3, ND4, ND4L, ND5, ND6). Subsequently, BAA destroyed the expression of Nrf2 antioxidant reaction genes (Nrf2, Keap1, HO‐1, NQO1, GCLM, GCLC). Furthermore, renal oxidative damage led to disorder in uric acid metabolism genes (Mrp2, Mrp4, Bcrp, OAT1, OAT2, OAT3) and exacerbated destruction in renal function. Overall, our study provided insights into the potential mechanism of BAA‐induced nephrotoxicity, which were important for the clinical monitoring and prevention of BAA.